Solasonine Causes Redox Imbalance and Mitochondrial Oxidative Stress of Ferroptosis in Lung Adenocarcinoma - Zeng, Yao-Ying; Luo, Ying-Bin; Ju, Xu-Dong; Zhang, Bo; Cui, Ya-Jing; Pan, Yan-Bin; Tian, Jian-Hui; Teng, Wen-Jing; Wu, Jianchun; Li, Yan (Frontiers in Oncology, 2022)
Ferroptosis, a type of iron-dependent oxidative cell death caused by excessive lipid peroxidation, is emerging as a promising cancer therapeutic strategy. Solasonine has been reported as a potential compound in tumor suppression, which is closely linked to ferroptosis. However, ferroptosis caused by solasonine is insufficiently identified and elaborated in lung adenocarcinoma, a fatal disease with high morbidity and mortality rates. First, the biochemical and morphological changes in Calu-1 and A549 cells exposed to solasonine are observed using a cell death assay and a microscope. The cell viability assay is performed after determining the executive concentration of solasonine to assess the effects of solasonine on tumor growth in Calu-1 and A549 cells. The ferroptosis is then identified by using ferroptosis-related reagents on CCK-8, lipid peroxidation assessment, Fe2+, and ROS detection. Furthermore, the antioxidant system, which includes GSH, Cys, GPx4, SLC7A11, and mitochondrial function, is measured to identify the potential pathways. According to the results, solasonine precisely exerts antitumor ability in lung adenocarcinoma cells. Ferroptosis is involved in the solasonine-induced cell death, as well as the accumulation of lipid peroxide, Fe2+, and ROS. Moreover, the failures of antioxidant defense and mitochondrial damage are considered to make a significant contribution to the occurrence of ferroptosis caused by solasonine. The study describes the potential process of ferroptosis caused by solasonine when dealing with lung adenocarcinoma. This encouraging evidence suggests that solasonine may be useful in the treatment of lung cancer.